2015
DOI: 10.1186/s13104-015-1351-1
|View full text |Cite
|
Sign up to set email alerts
|

Preventing hepatocellular carcinoma in Egypt: results of a Pilot Health Education Intervention Study

Abstract: BackgroundHepatocellular carcinoma (HCC), one of the most fatal malignancies, is particularly prevalent in Egypt, where we previously found deficiencies in knowledge concerning HCC and its risk factors. Hepatitis B and C viral infections are highly prevalent in Egypt, pesticides are very commonly used, and diets are often contaminated by aflatoxin, especially in rural areas.MethodsWe conducted a study to pilot test a health education intervention addressing HCC, its risk factors, and its main modes of preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…It also was effective in decreasing percent of poor knowledge about aflatoxins from 58.1% pre-intervention to1.1% post-intervention and in increasing percent of good knowledge score groups about aflatoxins from 41.9% pre-intervention to 98.9% postintervention, and this effect was statistically highly significant and was effective in decreasing percent of poor total knowledge about HCC and its risk factor prevention from 26.3% pre-intervention to 0% postintervention and in increasing percent of good total knowledge about HCC and prevention of its risk factors from 73.7% pre-intervention to 100% post-intervention, and this effect was statistically highly significant. This was in agreement with Saleh [14] who studied the effect of a pilot health education intervention about HCC prevention in Egypt and found that study participants had poor knowledge about HCC and its risk factors, and the health education intervention raised the knowledge of study participants on HCC and prevention of its risk factors.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It also was effective in decreasing percent of poor knowledge about aflatoxins from 58.1% pre-intervention to1.1% post-intervention and in increasing percent of good knowledge score groups about aflatoxins from 41.9% pre-intervention to 98.9% postintervention, and this effect was statistically highly significant and was effective in decreasing percent of poor total knowledge about HCC and its risk factor prevention from 26.3% pre-intervention to 0% postintervention and in increasing percent of good total knowledge about HCC and prevention of its risk factors from 73.7% pre-intervention to 100% post-intervention, and this effect was statistically highly significant. This was in agreement with Saleh [14] who studied the effect of a pilot health education intervention about HCC prevention in Egypt and found that study participants had poor knowledge about HCC and its risk factors, and the health education intervention raised the knowledge of study participants on HCC and prevention of its risk factors.…”
Section: Discussionsupporting
confidence: 88%
“…Not applicable 1 Epidemiology and Preventive Medicine Department, National Liver Institute, Gamal Abdel Nasser Street, Shebein El-Kom, Menoufia, Egypt. 2 Clinical Pathology Department, National Liver Institute, Gamal Abdel Nasser Street, Shebein El-Kom, Menoufia, Egypt.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily urinary AFM1 levels have been shown to be useful as a biomarker of internal aflatoxin B1 exposure in short-term intervention trials to determine efficacy of interventions (Mitchell et al, 2013). Further application of knowledge to practice is currently underway with numerous intervention/prevention studies, clinical trials, and education (Wild and Gong, 2010;Hoffmann et al, 2015;Saleh et al, 2015). The comprehensive approach used to create many successful preventive interventions to reduce health risks associated with aflatoxin is a model for the development, validation, and application of biomarkers for other environmental exposures (Wogan et al, 2012).…”
Section: Research/data Gapsmentioning
confidence: 99%
“…Hepatitis C viral infections are highly prevalent in Egypt, pesticides are very commonly used, and diets are often contaminated by aflatoxin, especially in rural areas (Saleh et al, 2015). Human hepatocellular carcinoma (HCC) is a heterogeneous disease, driven by different risk factors and presenting diverse clinicopathological features and outcomes (De Ponti et al, 2015).…”
Section: Genetic Unit Of Pediatric 3 Internal Medicine Departments mentioning
confidence: 99%